2022
DOI: 10.1177/20420188221112904
|View full text |Cite
|
Sign up to set email alerts
|

Timing of osteoporosis therapies following fracture: the current status

Abstract: In most patients, osteoporosis is diagnosed only after the occurrence of the first fragility fracture. It is of utmost importance to start osteoporosis medications immediately in these patients to prevent future fractures and also to reduce associated mortality and morbidity. There remains a hesitancy over initiating osteoporotic medications, specifically for antiresorptive agents like bisphosphonates following an acute fracture due to concern over their effect on fracture healing. The purpose of this review i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…Although taking Bps does potentially negatively affect the remodeling of the fracture callus, it will not lead to delayed healing 147 . So, it is still recommended to be used early in osteoporotic fractures 148 …”
Section: Anti‐osteoporosis Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although taking Bps does potentially negatively affect the remodeling of the fracture callus, it will not lead to delayed healing 147 . So, it is still recommended to be used early in osteoporotic fractures 148 …”
Section: Anti‐osteoporosis Therapiesmentioning
confidence: 99%
“…147 So, it is still recommended to be used early in osteoporotic fractures. 148 Currently, risedronate and ibandronate are only approved to treat PMOP. Alendronate and zoledronate are also authorized by the Food and Drug Administration (FDA) to increase bone mass in men with osteoporosis and treat glucocorticoid-induced osteoporosis and Paget's disease of bone (a chronic osteomatoid degeneration that can cause bone expansion, deformity and strength reduction).…”
Section: Bisphosphonatesmentioning
confidence: 99%
“…Osteoporosis can also afect the bone microarchitecture which also results in more complex healing of fractures and osseous defects [66]. Since implants are one of the most predictable treatment modalities to restore function and esthetics in hard tissues [67,68], the efect of osteoporosis on implant stability and survival rate has also been widely studied [69][70][71][72][73][74].…”
Section: Bone Regeneration For Implant Osseointegrationmentioning
confidence: 99%
“… 9 Another study showed that monoclonal antibody teriparatide may be effective for the treatment of osteoporotic fractures, but it was still controversial. 10 Therefore, clarifying the pathogenesis of OP at the molecular level and developing related drugs are becoming urgent requirements.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the main treatment methods for OP are drug therapy, such as estrogen, bisphosphonate, etc., but their side effects and poor oral absorption cannot be ignored 9 . Another study showed that monoclonal antibody teriparatide may be effective for the treatment of osteoporotic fractures, but it was still controversial 10 . Therefore, clarifying the pathogenesis of OP at the molecular level and developing related drugs are becoming urgent requirements.…”
Section: Introductionmentioning
confidence: 99%